artikel Pengaruh Promosi Terhadap Minat Menabung di Bank BSI pada Mahasiswa FEBI UIN Raden Mas Said Surakarta: Perbankan - Fahri Syafarudin (Business Finance Analyst Co., 2023)
The purpose of this study is to analyze the influence of promotion on the saving decisions of Bank Syariah Indonesia in students of Faculty of Islamic Economic and Business UIN Raden Mas Said Surakarta. This research is a quantitative research with a correlational approach. The type of data and data source used is primary data obtained through questionnaire tabulation from 92 respondents who are students of Faculty of Islamic Economic and Business UIN Raden Mas Said Surakarta and also being teh customers of Bank Syariah Indonesia. The data analysis method used is simple linear regression analysis. The results of the study revealed that promotion had a positive and significant effect on the saving decisions of Bank Syariah Indonesia. This research is expected to be able to provide information to Bank Syariah Indonesia and other parties related to what factors and which factors have the most influence on savings decisions at Bank Syariah Indonesia specially by the students in Faculty of Islamic Economic and Business UIN Raden Mas Said Surakarta.